ANTECEDENTS PENGEMBANGAN LOYALITAS PADA SERVICE RECOVARY MELALUI PERAN CUSTOMER TRUST - -, BADAWI - (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: This study aims to examine and analyze the mediating role of trust in the fairness of the development of customer loyalty. This research is a survey using a questionnaire given to the authorized service customer service in handling complaints (service recovery). A statistical technique used Structural Equation Modelling, individu analysis unit used the customers who have experienced or service recovery process a service vehicle two-wheeled motor Se-Cirebon region totaled 180 respondents. This study found that the justice handling complaints positive effect on trust Justice complaint against attitude and behavioral loyalty. Trust effect on behavioral loyalty and no effect on loyalty attitude. Mediates the effect of trust on loyalty justice grievance attitude and behavioral loyalty Key word: trust, justice, attitude loyality, behavior loyality